Hypothermic machine perfusion alleviates ischemia-reperfusion injury of intestinal transplantation in pigs - Hou, Wen; Yang, Shuang; Lu, Jiansen; Shi, Yuan; Chen, Jing; Chen, Decheng; Wang, Fei; Liu, Lei (Frontiers in Immunology, 2023)
Background Intestinal transplantation (IT) has become an important procedure for the treatment of irreversible intestinal failure. However, IT is extremely vulnerable to ischemia–reperfusion injury (IRI). Due to the limitations of static cold storage (SCS), hypothermic machine perfusion (HMP) is rapidly gaining popularity. In this study, the intestinal HMP system is established and HMP is compared with SCS. Methods An intestinal HMP system was built. Ten miniature pigs were randomly divided into the HMP and SCS groups, and their intestines were perfused using the HMP device and SCS, respectively, followed by orthotopic auto-transplantation. Analysis was done on the grafts between the two groups. Results Operation success rates of the surgery were 100% in both groups. The 7-day survival rate was 100% in the HMP group, which was significantly higher than that of the SCS group (20%, P< 0.05). The pathological results showed that fewer injuries of grafts were in the HMP group. Endotoxin (ET), IL-1, IL-6, IFN-γ and TNF-α levels in the HMP group were significantly lower than in the SCS group (P<0.05), whereas IL-10 levels were significantly higher (P<0.05).The intestinal expression levels of ZO-1 and Occludin were higher in the HMP group compared to the SCS group, whereas Toll-like receptor 4 (TLR4), nuclear factor kappa B (NFκB), and caspase-3 were lower.